Temperature gradient and microstructure evolution in AC flash sintering of 3 mol% yttria-stabilized zirconia. Issue 5 (4th April 2017) - Qin, Wei; Yun, Jondo; Thron, Andrew M.; van Benthem, Klaus
ABSTRACT: Systematic statistical analysis of the microstructural changes in 3 mol% yttria-stabilized zirconia was performed after flash sintering by alternating current (AC). The micrographs in the gauge section of the specimen were identical to those from DC flash sintered samples while no evident electrode effect was present for AC flash sintered samples. However, finite element modeling revealed a temperature gradient from the surface to the volume of the sintered body. Microstructure gradients, across the width of gauge section, were revealed for the AC flash sintered sample. Classical grain growth models due to Joule heating were insufficient in justifying the microstructural evolution under the simulated temperature distribution. Bimodal grain diameter distributions in flash sintered samples were observed. Therefore, it is proposed that faster grain growth mechanisms activated on a fraction of the grains by electric field/current occurred during flash sintering, and is responsible for the instantaneous grain growth.